POST PARTUM BLUES PADA IBU PRIMIPARA DAN KOMUNIKASI KELUARGA - Tikka Muslimah (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2022)
Post Partum Blues is a syndrome that appears in mothers who have just given birth. The signs of the post partum blues are depression reactions, crying, irritability, anxiety, unstable feelings. This risk will be greater for primiparous mothers or mothers who gave birth to their first child because they have no previous experience. Of course, family support is very important in alleviating the symptoms that occur, one of which is through family communication. So this study focuses more on curiosity to understand the post partum blues experience in primiparous mothers and the family communication that occurs in it. The formulation of the research problem is (1) how are the symptoms of post partum blues in primiparous mothers?; (2) what are the causes of post partum blues in primiparous mothers?; (3) how is the urgency of family communication to primiparous mothers?. This study uses a descriptive qualitative approach with phenomenological methods. The life experiences studied in this study were the experiences of primiparous mothers or mothers who gave birth to their first child with post partum blues syndrome and family communication that occurred. The results showed that the driving factors for the occurrence of Post Partum Blues include hormonal factors, childbirth, social pressure and physical fatigue. Primiparous mothers admit that one of the things that relieves the symptoms they experience is through communication with their families, especially husbands and parents. Effective family communication gives birth to openness, transfer of knowledge, conflict resolution and empathy.